(untitled) (Fiep Bulletin - online, 2013)
This essay begins with some concerns presented in the theoretical-practical field in the Physical Education that indicates to us there is a paradigm to be broken by teachers who develop such praxis, because so it seems, knowledge is centered to the "know-how". Thus, we need an understanding of physical education as praxis, the contradiction between theory and practice, in that they both intend daily. For this discussion we conducted a survey of basic nature.